The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/ijerph17176157
|View full text |Cite
|
Sign up to set email alerts
|

The Curated Food System: A Limiting Aspirational Vision of What Constitutes “Good” Food

Abstract: In an effort to elucidate an aspirational vision for the food system and explore whether the characteristics of such a system inadvertently set unattainable standards for low-wealth rural communities, we applied discourse analysis to the following qualitative datasets: (1) interviews with food experts and advocates, (2) scholarly and grey literature, (3) industry websites, and (4) email exchanges between food advocates. The analysis revealed eight aspirational food system discourses: production, distribution, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…It was clear that federal food assistance contributed to the participant's food security but was not the entire solution to address all of a family's food needs due to, in large part, affordability of adequate food. These findings are especially important to consider in context as rural households are often in communities with majority low-wage jobs, have higher rates of unemployment and underemployment, and have transportation barriers that limit access to food sources, increasing rural rates of food insecurity compared to urban counterparts [27][28][29]64] Limitations to this research exist. Given that the data was collected from 25 to 28 individuals across 6 diverse geographic, economic, ethnic, racial, and politically leaning counties in 6 different states, the research findings are limited in generalizability and should be interpreted with caution.…”
Section: Coping Mechanismsmentioning
confidence: 99%
“…It was clear that federal food assistance contributed to the participant's food security but was not the entire solution to address all of a family's food needs due to, in large part, affordability of adequate food. These findings are especially important to consider in context as rural households are often in communities with majority low-wage jobs, have higher rates of unemployment and underemployment, and have transportation barriers that limit access to food sources, increasing rural rates of food insecurity compared to urban counterparts [27][28][29]64] Limitations to this research exist. Given that the data was collected from 25 to 28 individuals across 6 diverse geographic, economic, ethnic, racial, and politically leaning counties in 6 different states, the research findings are limited in generalizability and should be interpreted with caution.…”
Section: Coping Mechanismsmentioning
confidence: 99%
“…Participatory approaches are recognised as an important endeavour in research addressing complex sustainability challenges (Karlsson et al, 2018). While some research has used participatory methods to identify visions for desirable food systems (Andress et al, 2020;Belisle-Toler et al, 2021;Foresight4Food, 2024) or food system indicators (Woodley et al, 2009;Carey and Dubbeling, 2017;Allen et al, 2019;Community Social Planning Council and Capital Region Food and Agriculture Initiatives Roundtable, 2020;Chaido Anthouli et al, 2022), we have only identified one food system-related initiative, on coastal fisheries, which has applied these methods in the identification of pathways to change along with relevant indicators (Secretariat of the Pacific Community, 2015). Another initiative worth noting here, is the Food Systems Analysis Toolkit, which has used participatory methods to develop indicators for three African countries to track progress along the UNFSS Action Tracks, however it also mapped these using adapted conventional frameworks (The Rockefeller Foundation, 2023).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Ajates [413]; Ajates [414]; Akinola et al [415]; Al Sidawi et al [416]; Alae-Carew et al [417]; Albert et al [418]; Al-Jawaldeh et al [419]; Allaby et al [388]; Amicarelli and Bux [420]; Amiri et al [421]; Amiri et al [422]; Andress et al [423]; April-Lalonde et al [424]; Aschemann-Witzel et al [425]…”
mentioning
confidence: 99%